Enej Silvij Piccolomini in slovenski prostor - Bogataj, Jan Dominik (Bogoslovni vestnik, 2024)
This paper discusses historical sources that testify to Aeneas Silvius Piccolomini’s contacts with present Slovenian territory. He already became well acquainted with the area in his role as secretary to Emperor Frederick III, then especially as Bishop of Trieste in 1447–1450, and finally as Pope Pius II, who confirmed the establishment of the Ljubljana diocese in 1463. The research focuses mainly on the period of his episcopacy in Trieste and investigates several new, hitherto unpublished documents (letters, documents) from this period. These shed new lights on his pastoral activity and question some of the long-accepted narratives of Slovenian historiography.
Keywords: cerkvena zgodovina; Church documents; Counts of Walsee; Diocese of Trieste; documents; ecclesiastical history; grofje Walsee; letters; listine; Pij; pisma; tržaška škofija